Message - Shahzad Aslam, Dr. Muhammad (Universal Journal of Pharmaceutical Research, 2016)
A diabetic wound is a big issue all around the world. Several researchers are working multi-disciplinary approach to finding the solution of wound healing. The healing of wound requires several stages such as hemostasis, inflammation, proliferation and tissue remodelling. The wound categorised into different types, and their therapy varies from chronic to acute. Debridement is the most crucial step in every kind of injury. The modern debridement methodologies include maggot debridement therapy, ultrasound-assisted wound debridement and solutions such as hypochlorous acid, nano copper solution. Nutritional based therapy is also famous for fast healing such as edible bird nest, Chromium and protein supplement. Acute wound could be treated with herbal ointment to reduce inflammation and modulate nitro oxide (Centella asiatica, Honey, garcina mangostana), collagen (Chitosan, hyaluronic acid), hydrogel (Indol-triazole scaffold hydrogel) whereas chronic wound is treated with modern therapies such as skin grafting, Negative-pressure wound therapy (NPWT), hyperbaric oxygen therapy, microcurrent therapy. A number of research is also going on wound dressing for faster healing such as polyurethane foam membrane dressing, Retro-Tech Dressing, activated carbon cloth, hydrocellular. For improving the granulation stage of wound healing, fish collagen, multilayer compression bandage have been used. The liquid wound dressing is also available in the market that gets solidify when exposed to air. We hope that our new articles will match the interest of the content that we currently publish and best wishes to all the team members of Universal Journal of Pharmaceutical Research.